Sejarah Peradaban Perekonomian Masa Sebelum Nubuwah dan Saat Masa Nubuwah (Rasulullah Saw) - Maula, Atiqatul; Latifah, Luluk (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
Economic development is now increasingly rapid along with the times, there are many records that say that the Islamic economy existed long before the conventional economy emerged. Based on the content in the verses of the Qur'an, especially about the stories of the Prophets and Apostles, it can be seen that economic practices have existed since the time of the Prophet Adam. While Islamic economic thought itself began since the revelation of the Qur'an and the lifetime of the Prophet at the end of the 6th century AD to the beginning of the 7th century AD. Starting with the life of Prophet Adam as the first creature created by Allah SWT, it has been explained in the Qur'an about his early life while in heaven which was then revealed to earth and how Prophet Adam lived a life on earth that was much different from in heaven, thus it can be concluded that It can be seen that the values of economics have actually existed since the first creature was created, namely the prophet Adam.Keywords: Islamic economics, before prophecy, the time of the Prophet